2018
DOI: 10.1111/epi.14052
|View full text |Cite
|
Sign up to set email alerts
|

Seizure detection using scalp‐EEG

Abstract: Scalp electroencephalography (EEG)-based seizure-detection algorithms applied in a clinical setting should detect a broad range of different seizures with high sensitivity and selectivity and should be easy to use with identical parameter settings for all patients. Available algorithms provide sensitivities between 75% and 90%. EEG seizure patterns with short duration, low amplitude, circumscribed focal activity, high frequency, and unusual morphology as well as EEG seizure patterns obscured by artifacts are g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
82
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 48 publications
2
82
0
8
Order By: Relevance
“…[1][2][3] Many factors contribute to this problem, with unrecognized and undocumented seizures being the most important. 8,9 Recently, many new EEG devices have appeared, combining various electrode configurations and data processing methods, [10][11][12][13][14][15] but none of these have been tested in real-life. These clinical problems also concern the patients, 6 and in the context of epilepsy research the problem of wrongful reporting is also well known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Many factors contribute to this problem, with unrecognized and undocumented seizures being the most important. 8,9 Recently, many new EEG devices have appeared, combining various electrode configurations and data processing methods, [10][11][12][13][14][15] but none of these have been tested in real-life. These clinical problems also concern the patients, 6 and in the context of epilepsy research the problem of wrongful reporting is also well known.…”
Section: Introductionmentioning
confidence: 99%
“…An EEG acquisition system usable during everyday life could be the tool currently lacking in the toolbox of epilepsy diagnostics and management. 8,9 Recently, many new EEG devices have appeared, combining various electrode configurations and data processing methods, [10][11][12][13][14][15] but none of these have been tested in real-life. In this study, we present the first real-life data on a subcutaneous EEG device for continuous home monitoring of epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…The seizure detection problem has even reached mainstream data science, with recent Kaggle competitions attracting thousands of entrants whose submissions covered a range of machine learning methods from deep convolutional neural networks to extreme gradient boosting [8][9][10]. A recent review of seizure detection from scalp EEG reported good performance from available algorithms, with sensitivities between 75% and 90% and false positive rates of between 0.1 and 5 per hour [6]. However, a large study of 1,478 ambulatory EEG studies found that commercially available automated detectors correctly identified electrographic seizures in only 53% of cases [11].…”
Section: Introductionmentioning
confidence: 99%
“…The primary methods used to detect seizures are detailed in reviews focusing on scalp EEG, surface electromyography (EMG), movement‐based detection, and multimodal seizure detection . Scalp EEG offers the unique advantage of capturing most seizure types, with high sensitivity (75%‐90%), but also a high rate of false alarms (0.1 and 5 per hour) . It is not currently adapted to chronic ambulatory recordings, although this might change with the development of subcutaneously implanted electrodes.…”
mentioning
confidence: 99%
“…9 Scalp EEG offers the unique advantage of capturing most seizure types, with high sensitivity (75%-90%), but also a high rate of false alarms (0.1 and 5 per hour). 6 It is not currently adapted to chronic ambulatory recordings, although this might change with the development of subcutaneously implanted electrodes. Surface EMG is typically used for detecting convulsive seizures, with 2 large-scale blinded prospective studies demonstrating high sensitivity (76%-100%) with average false-alarm rate ranging from 0.7 to 2.5/24 h. 7 Movement-based GTCS detection, primarily using accelerometry sensors, is associated with highly variable sensitivity (31%-95%) and positive predictive value (4%-60%) across video-EEG studies, whereas a field study reported even lower sensitivity (14%).…”
mentioning
confidence: 99%